Life in Extreme Environments - Diversity, Adaptability and Valuable Resources of Bioactive Molecules 2023
DOI: 10.5772/intechopen.110112
|View full text |Cite
|
Sign up to set email alerts
|

Genome Analysis Provides Insights into the Osmoadaptation Mechanisms of Halomonas titanicae

Abstract: Here, we report the osmoadaptation strategies adopted by the halotolerant species Halomonas titanicae BH1(T) inferred from genome sequence analysis. BH strain was isolated in 2010 from a rusticated sample collected in 1991 from the wreck of the Titanic, genome deposited in the database under the accession number (CP059082.1). It showed a high salt tolerance ranging from 0.5 to 25% NaCl (w/v) (optimal growth at 10% NaCl) with no growth in the absence of NaCl. The phylogenomic analysis showed that the BH1 strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Present study deals with characterization of the kdpFABC complex in the halotolerant bacterium A. xylosoxydans. Multiple studies identified the presence of kdp ATPaseencoding genes in many halotolerant bacteria, but no one has characterized this complex protein (Gumulya et al, 2018;González-Rosales et al, 2022;Najjari, 2023). Therefore, this is the first-ever study reporting the characterization of proteins constituting the kdp ATPase complex.…”
Section: Discussionmentioning
confidence: 99%
“…Present study deals with characterization of the kdpFABC complex in the halotolerant bacterium A. xylosoxydans. Multiple studies identified the presence of kdp ATPaseencoding genes in many halotolerant bacteria, but no one has characterized this complex protein (Gumulya et al, 2018;González-Rosales et al, 2022;Najjari, 2023). Therefore, this is the first-ever study reporting the characterization of proteins constituting the kdp ATPase complex.…”
Section: Discussionmentioning
confidence: 99%